Development and validation of the critical consciousness scale of environmental issues (CCS-EI): A RASCH model analysis - Supriyadi, Supriyadi; Haenilah, Een Yayah; Maulina, Dina (Biosfer: Jurnal Pendidikan Biologi, 2025)
The present study aimed to develop and validate the Indonesian-language version of the Critical Consciousness Scale of Environmental Issues (CCS-EI), specifically for higher education contexts. Employing Rasch analysis, the study rigorously examines the instrument’s reliability and validity through item fit statistics, rating scale functionality, and differential item functioning. The CCS-EI is designed to measure students' critical consciousness in environmental contexts, encompassing dimensions of critical reflection, critical motivation, and critical action. A diverse sample of 579 (male 87%; female 13%) participants from various university in Indonesia completed a 34-item of the CCS-EI. The sampling technique used is convenience sampling. Data were analysed using the Rasch model analysis, it was performed using the Winsteps version 5.6.1.0 software. The results of the Rasch analysis indicated that the reliability of the instrument was excellent (a = 0.91), item quality was excellent (1.00), and person reliability was consistent (0.91). In the validity aspect, all three domains of the CCS-EI exhibited unidimensionality, and a rating scale with four answer choices was deemed appropriate. The study also identifies item difficulty level in each dimension. Furthermore, the CCS-EI showed strong convergent validity, correlating significantly with existing measures of critical reflection, motivation, and action concerning environmental issues. This positions the CCS-EI as a reliable and valid instrument for use in various fields. Its ability to quantify critical consciousness provides valuable insights for designing educational evaluation and shaping policies that promote deeper engagement with environmental sustainability, contributing to both theoretical and practical advancements in the field.